Geometrical scaling law for laser-induced micro-projectile impact testing. (1st June 2022) - Gu, Z.P.; Cheng, Y.J.; Xiao, K.L.; Li, K.; Wu, X.Q.; Li, Q.M.; Huang, C.G.
Highlights: Geometrical scaling laws for the LIPIT with relative thick metallic film are obtained and validated for the first time. Numerical model of LIPIT is built, and the influences of the dimensionless parameters on the dimensionless launch speed of micro-projectiles are analyzed. Dimensionless formulas for predicting the launch speeds of micro-projectiles of LIPIT are proposed, rendering an effective method for analyzing and optimizing the LIPIT experiments. Abstract: Laser-induced micro-projectile impact testing (LIPIT) is a useful experimental method for exploring the dynamic behavior of materials at microscale. It has been a key issue to obtain a scaling law of launch velocity of LIPIT to simplify experimental design and improve experimental configuration. This paper obtains a geometrical scaling law of launch velocity for LIPIT with relative thick metallic film (30–80 µm thick aluminum) using dimensional analysis, experimental measurements, and numerical simulations. Firstly, the dimensional analyses of LIPIT with and without elastomer film configuration are performed, and the dimensionless parameters controlling the launch velocity of the micro-projectile are deduced, from which the geometrical scaling laws of launch velocity for the LIPIT are obtained. Then, the numerical simulation models of the LIPIT are established and validated by LIPIT experimental results, providing a numerical validation for the geometrical scaling laws. In addition, the influences of the dimensionless parameters on the dimensionless launch velocity of micro-projectiles are analyzed by numerical simulations, and the dimensionless formulas for predicting the launch velocities of micro-projectiles in a LIPIT are given, providing an effective method for analyzing and optimizing the LIPIT experiments. Graphical abstract: Image, graphical abstract